Emissões de gases do efeito estufa em sistemas multitróficos de aquicultura - Assunção, Marcelo Henrique Correa [UNESP] (2017)
The aim of this study was to investigate Greenhouse Gases (GHG) fluxes in aquaculture ponds. We tested if the use of Integrated Multi Trophic Aquaculture (IMTA) with Yellow tail tetra (Astyanax lacustris) and Amazon River prawn (Macrobrachium amazonicum) in a tropical environment changes the GHG flows in comparation with A. lacustris monoculture. We developed an experiment in earthen ponds with three treatments and four replications: monoculture (Tetra), two species free in the pond (Free IMTA) and fishes in cage and prawns free (Cage IMTA). Experiment ran 68 days between November and January 2016. We measured fluxes of carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O) with diffusive and dissolved methodologies. Mean of diffusive fluxes was -8.93 mg.m-2 .h-1 for CO2, -0.88 mg.m-2 .h-1 for CH4 e 1.78 mg.m-2 .h-1 for N2O. Concentration of CO2 oscillated between 0.0481 and 0.6668 mg.L-1 , CH4: 0.0003 and 0.0053 mg.L-1 e N2O: 0.0789 a 0.1177 mg.L-1 . Our results indicate variations over time, with higher fluxes at the beginning of experiment, decreasing over the growing period and trend of neutrality regarding to the GHG emissions at the end of experimental period.